Strategi Pengembangan UMKM dalam Pemanfaatan Hasil Perkebunan Buah Nanas di Desa Tanjung Baru - Enjellah, Enjellah; MH, Nisya Audya; Nastiar, Pikri Rajabi; Hidayatullah, Syarif; Setiawan, Budi; Meirisari, Vhika (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The development of Micro, Small, and Medium Enterprises (MSMEs) is one of the important efforts in improving the economy of rural communities. Tanjung Baru Village has abundant pineapple plantation potential, but the utilization of these plantation products is still not optimal. This service activity aims to formulate a strategy for the development of MSMEs through the use of pineapple plantation products in Tanjung Baru Village. The methods used include production skills training, managerial capacity building, and marketing assistance for processed pineapple products. The results of this activity showed a significant increase in participants' knowledge and skills, as evidenced by the increase in the average score from pre-test (41.0) to post-test (81.5). Participants succeeded in developing processed pineapple products such as jam, chips, and juice with good quality. This activity also resulted in training modules and partnership networks to support product marketing. It can be concluded that the MSME development strategy based on local potential implemented has succeeded in increasing the capacity of MSME actors in processing and marketing pineapple products, as well as opening up opportunities for business diversification that have the potential to increase the income of village communities.